MESIN PENGERING KERUPUK HEMAT ENERGI TINTUK MENINGKATKA}I PRODUKTIVIAS PRODIISEN KERUPUK - -, Sudiyatno -; S, Suprapto Rachmad (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
The objective of producing a low energy drying machine is to help chips industries in increasing their productivify by shortening the drying time. Up to now they use heat of sunlight to dry the chips. This process is rime consuming arrd why the dry season colnes, the process is delayed. It decreases the quality of chips. fhe drying machine produced uses firewood placed in a furnace as the heat source. The heat is then flown through pipes into the drying room, where wet chips are placed. ,,; The room has a length of 1.2 m, a height of I m and a width ot- I m. It has two doors and equipped with a thermometer. Below the room, there is a furnace having capacity cf 6 kg f-rre wood and an oxygen inlet. The drying temperature is 60 I kg firewood can produce the heat with temperature of 60 - 70o C for 1.5 hours.The drying process of wet chips takes about 5 hours, For that of half dry chips, it takes 2 hours. This machine has capacify of 2.400 rvet chips and 6.000 half dry chips.